PELATIHAN PEMBUATAN AKSESORIS RESIN LIMBAH CANGKANG KERANG BERBASIS DESAIN DAN PEMASARAN ONLINE SEBAGAI PELUANG WIRAUSAHA DESA WISATA PERCUT SEI TUAN - Pelawi, Yemima Christy; Juwairiah, Juwairiah; Maulana, Ananda; Sebayang, Grace Kezia; Fatmawati, Dhea; Lubis, Lisna Erliantika; Hutabarat, Oktaviasi; Simbolon, Wesly; Ramada, Daniel Hotma; Simamora, Imellianora; Simamora, Gabriel Saur Tua (Universitas Mataram, 2024)
Percut Sea Waters are located in Bagan Percut Village, Percut Sei Tuan District, Deli Serdang Regency, the majority of the population lives and depends on marine products. Bagan Percut Sei Tuan also has a floating culinary tour, resulting in a lot of leftover shells being thrown away from restaurants around the floating tour. One of the potentials that has not been utilized optimally is the potential for many shellfish that are thrown away to become waste and air pollution due to the smell and accumulation around the area. The aim of the service team is to increase the household income of fishermen in Percut Sei Tuan Village by carrying out waste utilization activities shells in the form of making handicrafts using design-based resin techniques and online marketing. This service method is empowering the community to process and utilize the potential of shellfish waste into creative craft products in the form of accessories and souvenirs. The service team's activities carry out counseling and courses that emphasize how to make crafts using resin techniques, making designs, and how to market the products online. The result of this service activity was the success of forming a new business for local housewives. The result of this service was the success of teaching how to process shellfish waste into resin accessories to housewives, teenagers and local figures. And succeeded in creating an e-commerce account selling shell crafts. And can increase people's income from the results of making crafts. The conclusion of this community service activity is the success of forming a new business and opening up livelihood opportunities for local residents.